2019
DOI: 10.1002/app.47792
|View full text |Cite
|
Sign up to set email alerts
|

Highly filled multilayer thermoplastic/graphene conducting composite structures with high strength and thermal stability for electromagnetic interference shielding applications

Abstract: Polyvinyl chloride (PVC)/graphene and poly(methyl methacrylate) (PMMA)/graphene nanocomposites were made by solution casting technique with graphene weight fractions of 1, 5, 10, 15, and 20%. Multilayer structures of the composites were made by hot compression technique to study their electromagnetic interference shielding effectiveness (EMI SE). Tensile strength, hardness, and storage modulus of the nanocomposites were studied in relation with graphene weight fraction. There has been a substantial increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…21 By virtue of the segregated structure formed in LLDPE matrix, the MGO can effectively enhance electrical property of LLDPE matrix without additional reduction as shown in Figure 5a. Firstly, the volume resistance of the HDPE-MGO gradually decreased with the increasing of the MGO loadings due to the high contract area and conductivity, 24 the volume resistance is 6.23 ± 0.32 E, 4 2.65 ± 0.34 E, 3 3.84 ± 0.46 E 2 and 1.25 ± 0.09 E 2 ΩÁm at the adding loadings of MGO in 5, 10, 15, and 20 wt%, respectively. After diluting 10 times in LLDPE by meltmixed method and forming the segregated structure, the electrical property of LLDPE/HDPE-MGO reaches the antistatic level (volume resistance: 2.61 ± 0.15 E 7 ΩÁm) with the loading of 2 wt% MGO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 By virtue of the segregated structure formed in LLDPE matrix, the MGO can effectively enhance electrical property of LLDPE matrix without additional reduction as shown in Figure 5a. Firstly, the volume resistance of the HDPE-MGO gradually decreased with the increasing of the MGO loadings due to the high contract area and conductivity, 24 the volume resistance is 6.23 ± 0.32 E, 4 2.65 ± 0.34 E, 3 3.84 ± 0.46 E 2 and 1.25 ± 0.09 E 2 ΩÁm at the adding loadings of MGO in 5, 10, 15, and 20 wt%, respectively. After diluting 10 times in LLDPE by meltmixed method and forming the segregated structure, the electrical property of LLDPE/HDPE-MGO reaches the antistatic level (volume resistance: 2.61 ± 0.15 E 7 ΩÁm) with the loading of 2 wt% MGO.…”
Section: Resultsmentioning
confidence: 99%
“…Electrically conductive polymer composites (CPCs) have attracted considerable academic and industrial attentions due to the easy processing, adjustable electrical properties, and low cost 1 . It has been widely employed in anti‐static materials, 2 electromagnetic interface, 3,4 sensor, 5 and conductors 6,7 . Actually, most of the ordinary host polymers are essentially insulating, after incorporating the conductive filler, the composites will exhibit an insulator/conductor transition when the conductive filler reach a critical value (percolation threshold: φ c ), where the conductive network get constructed.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that multilayered structures constituted by absorbing composite layers can provide better EM radiation attenuation (decrease of RL) with outstanding broad bandwidth, which is attributed to the increase of multi‐reflection and scattering of the radiation between conductive layers 62,63 . These structures can be arranged as stacked layers with similar composition 22 or different compositions with different conductivity values 64 . The arrangement of the different layers also contributes for broadening the frequency range with improved EM attenuation 15 .…”
Section: Resultsmentioning
confidence: 99%
“…21 Joseph et al reported a conductivity of 10 −5 S m −1 and EMI SE of around 13 dB for the PMMA/ GNP composites containing 10 wt% of GNP and prepared by solution blending. 22,23 Zhang et al achieved EMI SE of around 3.5 dB with the addition of 2 wt% of GNP in PMMA by solution process. 24 Zakiyan et al also reported an EMI SE of around 3 dB with the presence of 3 wt% of GNP in the PMMA composite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation